PERILAKU POLITIK MASYARAKAT DALAM PEMILIHAN KEUCHIK DI GAMPONG PANGGE PILOK KECAMATAN GRONG GRONG KABUPATEN PIDIE PERIODE 2022-2027 - Zulfikar Zulfikar; Rozailli Rozailli (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
The provisions for the election of village heads have been regulated in many regulations, both in Law Number 6 of 2014 concerning villages, as well as in the form of Aceh Qanun Number 4 of 2014 concerning villages. So that it can be formulated, how is the behavior of the community in the election of the keuchik in Pangge Pilok Village? As well as the factors behind the political behavior of the community in the election of the keuchik in the village of pangge pilok, so that it can be known the behavior and goals of the community of pangge pilok who played a role in the election of the keuchik in the village of pangge pilok. The research method applied is qualitative, data sourced from primary and secondary with a total of 15 informants consisting of each community representative, through observation, interviews and documentation. The results of this study indicate that the Political Behavior of the Community in the Election of Keuchik in Pangge Pilok Village, Grong Grong District, Pidie Regency, is generally determined by internal factors as well as external factors. In addition, some other people chose the Keuchik candidate because they had a family relationship with one of the candidates. The village head candidate has innovative and transparent behavior, because the village head that the community wants is a village head candidate who is transparent in any way and has innovations that can build Pangge Pilok village even better in the future. Implementation of the election shows that the interest and participation rate of the community on election day is very high so that the event runs smoothly.Keywords: Behavior, Election, Keuchik